Factors That Hinder Female Employees Career Development in the Public Sector Organisations in Libya - Abdullatif, Ahmed Saleh (2010)
This study examined the Factors that hinder female employees career development in the public sector organisations in Libya.This is to examine the influence of the factors i.e. gender stereotyping societal culture and glass ceiling on women advancement in organizations in Libya .The result shows all the variables are related with the result showing moderate relationship .A multiple regression was also conducted to see the variance among variables.